Ph.d. i en tangotid - Weidner, Ida; Normann, Jan (Psyke & Logos, 2015)
The present article discusses the dilemmas, possibilities, and consequences that originate from increased external funding of research in the humanities and social sciences, including psychology. This development in funding affects these sciences as they are no longer defined by a criterion of truth, but become part of a performativity culture. By employing Davies & Harré’s (1990) positioning theory and Lyotard’s (1996) concept of performativity, this article explores the possibilities and consequences of the dilemmas researchers face when research is increasingly financed externally.